Self-assembled nanoparticles comprising aptide–SN38 conjugates for use in targeted cancer therapy. (2nd November 2016) - Kim, Hyungjun; Lee, Yonghyun; Kang, Sukmo; Choi, Minsuk; Lee, Soyoung; Kim, Sunghyun; Gujrati, Vipul; Kim, Jinjoo; Jon, Sangyong
Abstract: Self-assembled nanoparticles (NPs) have been intensively utilized as cancer drug delivery carriers because hydrophobic anticancer drugs may be efficiently loaded into the particle cores. In this study, we synthesized and evaluated the therapeutic index of self-assembled NPs chemically conjugated to a fibronectin extra domain B-specific peptide (APTEDB ) and an anticancer agent SN38. The APTEDB –SN38 formed self-assembled structures with a diameter of 58 ± 3 nm in an aqueous solution and displayed excellent drug loading, solubility, and stability properties. A pharmacokinetic study revealed that the blood circulation half-life of SN38 following injection of the APTEDB –SN38 NPs was markedly higher than that of the small molecule CPT-11. The APTEDB –SN38 NPs delivered SN38 to tumor sites by both passive and active targeting. Finally, the APTEDB –SN38 NPs exhibited potent antitumor activities and low toxicities against EDB-expressing tumors (LLC, U87MG) in mice. This system merits further preclinical and clinical investigations for SN38 delivery.